Coats plus syndrome: a rare cause of severe gastrointestinal tract bleeding in children - a case report - Selcen Bozkurt; Ayse Merve Usta; Nafiye Urganci; Nida Gulderen Kalay; Gulsen Kose; Evrim Ozmen (BMC, 2022)
Abstract Background Coats plus syndrome, cerebroretinal microangiopathy with calcifications and cysts, is a rare disease with autosomal recessive pattern occurring due to a mutation in CTC1, encoding conserved telomere maintenance component 1, gene. Besides retinal involvement, abnormalities in brain and osteopenia, serious life-threatening bleeding in gastrointestinal tract and portal hypertension can be observed. Case presentation A 6-year-old girl with Coats plus syndrome presented to the pediatric emergency department with vomiting blood and blood in stool. An upper and lower gastrointestinal endoscopy revealed esophageal varices and vascular telangiectasia in the pyloric antrum, duodenum, and colon. She received palliative care and the bleeding was stopped after receiving intravenous octreotide. She then was followed in the pediatric gastroenterology, neurology, and ophthalmology clinics. She was later hospitalized and admitted to the intensive care unit as she continued to have intermittent gastrointestinal system bleeding. She eventually died due to severe gastrointestinal system bleeding. Conclusions Coats plus syndrome can lead to life-threatening gastrointestinal bleeding and portal hypertension. As Coats plus syndrome is quite rare, there is little published data on this syndrome. This report presents a case of Coats plus syndrome as a rare cause of gastrointestinal bleeding and portal hypertension.